Evaluation of Two New Automated Assays for Hepatitis B Virus Surface Antigen (HBsAg) Detection: IMMULITE HBsAg and IMMULITE 2000 HBsAg - Weber, Bernard (American Society for Microbiology, 2003)
In recent years the diagnostic industry has developed new automated immunoassays for the qualitative detection of hepatitis B virus (HBV) surface antigen (HBsAg) in serum and plasma samples that are performed on analyzers that permit a high-speed throughput, random access, and primary tube sampling. The aim of the present study was the evaluation of two new automated HBsAg screening assays, IMMULITE HBsAg and IMMULITE 2000 HBsAg, from Diagnostic Products Corporation. The new HBsAg assays were compared to well-established tests (Auszyme Monoclonal [overnight incubation, version B], IMx HBsAg, AxSYM HBsAg, and Prism HBsAg [all from Abbott] and Elecsys HBsAg [Roche Diagnostics]). In the evaluation were included seroconversion panels, sera from the acute and chronic phases of infection, dilution series of various HBsAg standards, HBV subtypes and S gene mutants. To challenge the specificity of the new assays, sera from HBsAg-negative blood donors, pregnant women, and dialysis and hospitalized patients and potentially cross-reactive samples were investigated. IMMULITE HBsAg and IMMULITE 2000 HBsAg, although not as sensitive as the Elecsys HBsAg assay, were equivalent to the AxSYM HBsAg assay and showed a higher sensitivity than the Auszyme Monoclonal B and IMx HBsAg systems for detection of acute infection in seroconversion panels. The specificities (100%) of both IMMULITE assays on unselected blood donors and potentially interfering samples were comparable to those of the alternative assays after repeated testing. In conclusion, the new IMMULITE HBsAg and IMMULITE 2000 HBsAg assays show a good sensitivity for HBsAg detection compared to other well-established tests. The specificity on repeatedly tested samples was equivalent to that of the alternative assays. The rapid turnaround time, primary tube sampling, and on-board dilution make it an interesting assay system for clinical laboratory diagnosis.